The Role of Transformational Leadership and Digital Culture in Enhancing Employee Agility and Readiness to Adapt to Change Among Employees in Indonesia’s Telecommunications Sector - Setyowati Subroto; Rully Fildansyah; Muhamad Ammar Muhtadi (Westscience Press, 2026)
The rapid advancement of digital technologies has significantly transformed the telecommunications industry, requiring organizations to develop adaptive employees capable of responding effectively to continuous change. In this dynamic environment, employee agility and readiness to adapt to change have become essential capabilities for maintaining organizational competitiveness. This study aims to examine the role of transformational leadership and digital culture in enhancing employee agility and readiness to adapt to change among employees in Indonesia’s telecommunications sector. This research employed a quantitative approach using survey data collected from 155 employees working in telecommunications companies in Indonesia. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The analytical procedures included validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis to examine the proposed relationships among variables. The results indicate that transformational leadership has a positive and significant effect on employee agility and readiness to adapt to change. Furthermore, digital culture significantly influences employee agility and demonstrates the strongest effect on readiness to adapt to change. These findings highlight that effective leadership practices and a supportive digital culture are critical factors in developing an adaptive workforce capable of navigating technological disruption. The study contributes to the literature on digital transformation by emphasizing the importance of human-centered organizational capabilities in achieving successful transformation outcomes. Practically, telecommunications companies should strengthen transformational leadership competencies and cultivate digital-oriented organizational cultures to improve employee adaptability and organizational resilience.